ANALYZING ECONOMIC EFFICIENCY IN GOURAMI FISH FARMING IN KEDUNGLANGKAP VILLAGE: A QUALITATIVE CASE STUDY - Achmad Syaikhon Kabir; Rusmini (Jurnal Dinamika Ekonomi Syariah, 2025)
This research aims to analyze the economic efficiency of tilapia farming in Kedunglangkap Village, an area with promising aquaculture potential. Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation studies involving farmers, village officials, and related business actors. The results indicate that tilapia farming in this village is predominantly small to medium scale, with most farmers utilizing concrete ponds and relying on water sources from rivers. Factors determining economic efficiency include feed prices, operational costs, marketing networks, as well as risks related to diseases and climate. The majority of farmers expressed that this venture is profitable and feasible for development, especially if supported by good management and improved infrastructure. This study recommends enhancing supporting infrastructure, diversifying feed, providing training for farmers, and developing marketing networks as strategic steps to improve economic efficiency and the sustainability of tilapia farming in Kedunglangkap Village.